PLAGIOCLASE-RICH CHONDRULES IN THE REDUCED CV CHONDRITES: EVIDENCE FOR COMPLEX FORMATION HISTORY AND GENETIC LINKS BETWEEN CALCIUM-ALUMINUM-RICH INCLUSIONS AND FERROMAGNESIAN CHONDRULES - Krot A.N.; Hutcheon I.D.; Keil K. (My University, 2002)
Plagioclase-rich chondrules (PRCs) in the reduced CV chondrites Efremovka, Leoville, Vigarano and Grosvenor Mountains (GRO) 94329 consist of magnesian low-Ca pyroxene, Al-Ti-Cr-rich pigeonite and augite, forsterite, anorthitic plagioclase, FeNi-metal-sulfide nodules, and crystalline mesostasis composed of silica, anorthitic plagioclase and Al-Ti-Cr-rich augite. The silica grains in the mesostases of the CV PRCs are typically replaced by hedenbergitic pyroxenes, whereas anorthitic plagioclase is replaced by feldspathoids (nepheline and minor sodalite). Some of the PRCs contain regions that are texturally and mineralogically similar to type I chondrules and consist of forsterite, low-Ca pyroxene and abundant FeNi-metal nodules. Several PRCs are surrounded by igneous rims or form independent compound objects. Twelve PRCs contain relic calcium-aluminum-rich inclusions (CAIs) composed of anorthite, spinel, high-Ca pyroxene, ± forsterite, and ± Al-rich low-Ca pyroxene. Anorthite of these CAIs is generally more heavily replaced by feldspathoids than anorthitic plagioclase of the host chondrules. This suggests that either the alteration predated formation of the PRCs or that anorthite of the relic CAIs was more susceptible to the alteration than anorthitic plagioclase of the host chondrules. These observations and the presence of igneous rims around PRCs and independent compound PRCs suggest that the CV PRCs may have had a complex, multistage formation history compared to a more simple formation history of the CR PRCs. Relatively high abundances of moderately-volatile elements such as Cr, Mn and Si in the PRCs suggests that these chondrules could not have been produced by volatilization of ferromagnesian chondrule precursors or by melting of refractory materials only. We infer instead that PRCs in carbonaceous chondrites formed by melting of the reduced chondrule precursors (magnesian olivine and pyroxene, FeNi-metal) mixed with refractory materials (relic CAIs) composed of anorthite, spinel, high-Ca pyroxene, and forsterite. The mineralogical, chemical and textural similarities of the PRCs in several carbonaceous chondrite groups (CV, CO, CH, CR) and common presence of relic CAIs in these chondrules suggest that PRCs may have formed in the region(s) intermediate between the regions where CAIs and ferromagnesian chondrules originated.